Time-Varying Neutral Interest Rate-The Case of Brazil - Perrelli, Roberto (IMF Working Papers; Working Paper ;, 2014)
Emerging markets have experienced a sizeable decline in their neutral real interest rates until recently. In this paper we try to identify the main factors that contributed to it, with a focus on Brazil. We estimate an interval for Brazil's time-varying neutral rate based on a range of structural and econometric models. We assess the implications of incorrectly estimating a time-varying neutral rate using a small structural model with a simple monetary policy instrument rule. We find that policy prescriptions are very different when facing uncertainty of neutral rate and of output gap. Our result contrasts sharply with Orphanides (2002), suggesting that the best response to neutral rate uncertainty is to ensure policy remains highly sensitive to inflation and output variations.